9x-3=6x+5

Simple and best practice solution for 9x-3=6x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-3=6x+5 equation:


Simplifying
9x + -3 = 6x + 5

Reorder the terms:
-3 + 9x = 6x + 5

Reorder the terms:
-3 + 9x = 5 + 6x

Solving
-3 + 9x = 5 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-3 + 9x + -6x = 5 + 6x + -6x

Combine like terms: 9x + -6x = 3x
-3 + 3x = 5 + 6x + -6x

Combine like terms: 6x + -6x = 0
-3 + 3x = 5 + 0
-3 + 3x = 5

Add '3' to each side of the equation.
-3 + 3 + 3x = 5 + 3

Combine like terms: -3 + 3 = 0
0 + 3x = 5 + 3
3x = 5 + 3

Combine like terms: 5 + 3 = 8
3x = 8

Divide each side by '3'.
x = 2.666666667

Simplifying
x = 2.666666667

See similar equations:

| X^2+1=4+2x-x^2 | | M/5+(3m-6)/2=2m-6 | | 2.8(t-6)+1=9.4 | | 3(s+1.78)=11.67 | | 183-p=851 | | ((24x)/(884-24x))=1 | | 10(b+235)=760 | | 3g+6=18 | | 0=a^2-20a+96 | | A^2-20a=96 | | 4(h-554)=896 | | 31-3(x+1)=3x | | ((2p)/(p+6))=1 | | -7(u+-5)=-56 | | 5x+10=8x+4 | | 42+7k=21 | | -3.28=2(1.5y-.5) | | x^2-36=-9 | | y=5x-40 | | (q+1)(2q-3)=3 | | 2x+4=3x-10 | | 9(h-84)-5=77 | | (7y)/(7y+7)+(7y-17)/(6y+6)=(6y+1)/(y+1) | | |36-7|=27 | | o/9+13=-3 | | 0/9+13=-3 | | 2/3v+1/6-7/9-5/6 | | 7y/(7y+7)+(7y-17)/(6y+6)=(6y+1)/(y+1) | | (31/5)y=31 | | 5N(N-1)=N+8 | | 12-9x=17-8x | | 31/5y=31 |

Equations solver categories